The Neurochemical Mobile with Non-Linear Interaction Matrix: An Exploratory Computational Model - Qi, Z.; Fieni, D.; Tretter, F.; Voit, E. O. (Pharmacopsychiatry, 2013)
Several years ago, the “neurochemical mobile” was introduced as a visual tool for explaining the different balances between neurotransmitters in the brain and their role in mental disorders. Here we complement this concept with a non-linear computational systems model representing the direct and indirect interactions between neurotransmitters, as they have been described in the “neurochemical interaction matrix.” The model is constructed within the framework of biochemical systems theory, which facilitates the mapping of numerically ill-characterized systems into a mathematical and computational construct that permits a variety of analyses. Simulations show how short- and long-term perturbations in any of the neurotransmitters migrate through the entire system, thereby affecting the balances within the mobile. In cases of short-term alterations, transients are of particular interest, whereas long-term changes shed light on persistently altered, allostatic states, which in mental diseases and sleep disorders could be due to a combination of unfavorable factors, resulting from a specific genetic predisposition, epigenetic effects, disease, or the repeated use of drugs, such as opioids and amphetamines.
Keywords: allostasis; biochemical systems analysis; brain chemistry; computational systems biology; homeostasis; network analysis; neurotransmitter